Modified PP material and preparation method thereof, vehicle and battery
By adding potassium aluminum silicate and other additives to the PP material and using its unique nanosheet structure, the problems of poor heat resistance and dimensional stability of PP materials are solved, and modified PP materials with high heat resistance, high dimensional stability and low shrinkage are achieved, which are suitable for applications in the equipment manufacturing industry.
Patent Information
- Application Number
- CN202510043519.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-04
AI Technical Summary
There are problems of poor heat resistance, poor dimensional stability and high shrinkage during molding, storage and use of existing PP materials, which affects their application in the equipment manufacturing industry.
By adding potassium aluminum silicate to the PP main material, the "skeleton" support is formed using its unique two-dimensional nanosheet layer structure, and combining PP-g-MAH, coupling agents and antioxidants, the heat resistance, dimensional stability and compatibility of PP materials are improved.
It improves the heat resistance, dimensional stability and compressive resistance of PP materials, reduces the molding shrinkage rate, enhances the comprehensive performance of the materials, and is suitable for applications in the equipment manufacturing industry.
Smart Images

Figure CN119752037A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a modified PP material and a preparation method thereof, a vehicle and a battery. Background Art
[0002] The equipment manufacturing industry covers a wide range of fields, including various products in daily life, equipment production in various industries, military equipment, etc., which are all produced by the equipment manufacturing industry, including machinery, electronics, light industry, metallurgy, petrochemicals, textiles, medicine, food, military industry, etc. Polypropylene (PP) is widely used in the equipment manufacturing industry due to its light weight, good rigidity, flexural resistance, and low temperature impact resistance, heat resistance and aging resistance through directional modification, such as automotive interior, automotive accessories, rigid packaging, battery casing and other fields. In addition, it has sufficient sources and low prices. In recent years, it has gradually become a large-volume polymer material in the equipment manufacturing industry. However, due to its high molding shrinkage and poor dimensional stability, the injection molding, storage and use of the product are often accompanied by poor heat resistance, warping deformation, unqualified dimensions, and difficulty in demolding, which seriously affects its matching application in the equipment manufacturing industry. Therefore, it is very important to study the influencing factors of the shrinkage and heat resistance of modified PP materials. Summary of the invention
[0003] The present invention aims to solve or improve the technical problems of poor heat resistance and poor dimensional stability of PP materials in the prior art.
[0004] The first aspect of the present invention is to provide a modified PP material.
[0005] The second aspect of the present invention is to provide a method for preparing a modified PP material.
[0006] A third aspect of the present invention is to provide an electronic vehicle.
[0007] A fourth aspect of the present invention is to provide a battery.
[0008] The modified PP material provided by the present invention comprises raw materials for preparing the modified PP material including a PP main material, an inorganic powder and an auxiliary agent; the mass percentage of the PP main material in the modified PP material is greater than or equal to 30% and less than or equal to 90%; the mass percentage of the inorganic powder in the modified PP material is less than or equal to 60%; the mass percentage of the auxiliary agent in the modified PP material is less than or equal to 20%; the inorganic powder comprises potassium aluminum silicate, the molecular formula of potassium aluminum silicate is SiO2·Al2O3·K2O, and the structure of potassium aluminum silicate is a lamellar structure; the auxiliary agent comprises PP-g-MAH (maleic anhydride grafted polypropylene), a coupling agent and an antioxidant.
[0009] The modified PP material provided by the present invention is prepared by adding potassium aluminum silicate to the main PP material. Since potassium aluminum silicate has a unique two-dimensional nanosheet structure, a "skeleton" support is formed, so that the modified PP material has good heat resistance and dimensional stability, which helps to improve the compressive resistance of PP when heated, and the shrinkage rate during molding is low.
[0010] In addition, the present application also adds PP-g-MAH, which serves as a compatibilizer to improve the compatibility between the PP main material and potassium aluminum silicate, thereby making the modified PP material have excellent comprehensive properties.
[0011] The coupling agent is used to activate the surface of potassium aluminum silicate, which helps to enhance the compatibility between the PP main material and potassium aluminum silicate and improve the dispersibility of inorganic powder in PP resin.
[0012] The addition of antioxidants helps to improve the aging resistance of modified PP materials.
[0013] In some embodiments, optionally, the mass percentage of the PP main material in the modified PP material is greater than or equal to 50%, and less than or equal to 70%; the mass percentage of the inorganic powder in the modified PP material is greater than 20%, and less than or equal to 40%.
[0014] In this embodiment, the content of inorganic powder is further increased, so that the addition of a large amount of inorganic powder further improves the high heat resistance, high dimensional stability, low shrinkage, high strength and other properties of the modified PP material. Of course, the content of inorganic powder cannot be too high, as too high a content of inorganic powder will reduce the content of the PP main material, thereby destroying the basic properties of the PP main material.
[0015] In some embodiments, optionally, the content of the PP main material is 50%, 60% or 70%, and the content of the inorganic powder is 20%, 30% or 40%.
[0016] In some embodiments, optionally, the coupling agent includes one or a combination of the following: silane 550 (vinyl triethoxy silane), silane 560 (γ-aminopropyl triethoxy silane), and aluminum-titanium composite coupling agent LD.
[0017] In this embodiment, silane 550, silane 560 and aluminum-titanium composite coupling agent LD are very suitable as compatibilizers between the PP main material and potassium aluminum silicate, thereby greatly improving the dispersibility of the inorganic powder in the PP resin.
[0018] In some embodiments, the antioxidant optionally includes antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) and / or antioxidant 168 (tris(2,4-di-tert-butylphenyl)phosphite).
[0019] In some embodiments, optionally, the mass percentage of PP-g-MAH in the modified PP material is less than or equal to 15%.
[0020] In this embodiment, the mass percentage of PP-g-MAH in the modified PP material is less than or equal to 15%. For example, it can be 5%-10% (it should be understood that in order to make the solution more concise and clear, the values at both ends of all ranges in this application are inclusive, 5%-10% is greater than or equal to 5%, and less than or equal to 10%, and the same applies to the other range values). For example, the mass percentage of PP-g-MAH is equal to 5%, 8% or 10%.
[0021] In some embodiments, the coupling agent may be less than or equal to 2% by mass of the modified PP material, for example, 1% or 2%.
[0022] In some embodiments, the antioxidant may be present in an amount greater than or equal to 1% and less than or equal to 3% by mass of the modified PP material, for example, 1%, 2% or 3%.
[0023] In some embodiments, optionally, the inorganic powder further includes calcium carbonate and mica flakes.
[0024] In this embodiment, the addition of calcium carbonate in an appropriate amount can improve the fluidity of the material, thereby improving its processing performance. It also helps to improve the dimensional stability of the finished product, especially reducing shrinkage during injection molding. In addition, calcium carbonate can also slightly increase the hardness and rigidity (i.e., Young's modulus) of the material. The addition of mica flakes can improve heat resistance and electrical insulation. Most importantly, the layered structure of mica flakes can form a barrier inside the material, slowing down the penetration of gases, liquids and other substances, which helps to improve the protective properties of the modified PP material.
[0025] In some embodiments, optionally, the mass proportions of potassium aluminum silicate, calcium carbonate and mica flakes are the same. Of course, the sum of the mass proportion of calcium carbonate and the mass proportion of mica flakes can also be equal to the mass proportion of potassium aluminum silicate.
[0026] In some embodiments, optionally, the thickness of the potassium aluminum silicate sheet is greater than or equal to 30 nm and less than or equal to 60 nm, and the particle size of the potassium aluminum silicate is greater than or equal to 1 μm and less than or equal to 10 μm. Optionally, the thickness of the potassium aluminum silicate sheet is greater than or equal to 40 nm and less than or equal to 50 nm, such as 40 nm or 50 nm. Optionally, the particle size of the potassium aluminum silicate is greater than or equal to 4 μm and less than or equal to 8 μm. For example, 4 μm, 6 μm or 8 μm.
[0027] In this embodiment, the thickness of the potassium aluminum silicate flakes is further limited to ensure the stability of the modified PP material when heated, and the particle size of the potassium aluminum silicate is further limited to improve the dispersibility of the potassium aluminum silicate in PP, thereby ensuring the overall comprehensive performance of the modified PP material.
[0028] In some embodiments, optionally, the grafting rate of PP-g-MAH is greater than or equal to 0.1% and less than or equal to 1.5%.
[0029] In this embodiment, if the grafting rate is too low, PP-g-MAH cannot effectively improve the compatibility between the matrix resin and the filler, resulting in uneven dispersion, which may form larger particles or agglomeration, affecting the mechanical properties, dimensional stability and heat resistance of the final product. Too high a grafting rate may increase the melt viscosity, making the material more difficult to process, such as poor flow during injection molding. Optionally, the grafting rate is equal to 1%.
[0030] The second aspect of the present application provides a method for preparing a modified PP material, which is used to prepare a modified PP material as any embodiment of the first aspect of the present application, and the method for preparing the modified PP material comprises: placing potassium aluminum silicate in an ethanol solution, adding a coupling agent to the ethanol solution to obtain a mixture, stirring and ultrasonically oscillating the mixture to perform surface activation treatment on the potassium aluminum silicate, and separating the activated potassium aluminum silicate; mixing the PP main material and PE-g-MAH to obtain a main material premix; mixing the activated potassium aluminum silicate and an antioxidant to obtain a mixed material; and extruding the main material premix and the mixed material in an extruder to obtain a modified PP material.
[0031] The preparation method of the modified PP material provided in the present application is to firstly perform surface activation on potassium aluminum silicate. Specifically, the potassium aluminum silicate inorganic powder is placed in a 90% ethanol solution, and then a quantitative silane coupling agent is added. The potassium aluminum silicate is surface activated by high-speed stirring (3000 rpm, 10 minutes) and ultrasonic vibration (40KHz, 4h), and then the activated potassium aluminum silicate is blown and dried (temperature 80°C) to obtain an activated inorganic filler A. Then, the PP main material and the PP-g-MAH matrix resin are introduced into a high-speed mixer according to the formula ratio and premixed for 2 minutes to obtain a main material premix B. Then, the activated inorganic filler A and the antioxidant are introduced into a high-speed mixer according to the ratio for premixing, the mixing temperature is 40°C-50°C, and the mixture is stirred at a low speed of 50 rpm for 5 minutes to obtain a mixed material C. Finally, the main material premix B and the mixed material C are added into the twin-screw extruder from the main feeding port and the side feeding port respectively. The feeding speed is adjusted to match the material ratio, the extruder temperature is 190℃-220℃, the screw speed is 180 rpm-220 rpm, the extrusion strands are cooled and granulated to obtain the high heat-resistant modified PP material of the present application.
[0032] A third aspect of the present invention provides a vehicle, the manufacturing material of the vehicle at least includes a modified PP material as described in any technical solution of the first aspect of the present application.
[0033] The fourth aspect of the present invention provides a battery, wherein the preparation material of the battery at least includes the modified PP material according to any technical solution of the first aspect of the present application.
[0034] Additional aspects and advantages of the present invention will become apparent in the following description or may be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The above and / or additional aspects and advantages of the embodiments of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0036] Figure 1 A schematic flow chart of a method for preparing a modified PP material provided in an embodiment of the present invention is shown;
[0037] Figure 2 The scanning electron microscope image of the morphology of the nanosheet potassium aluminum silicate provided by the embodiment of the present invention is shown. DETAILED DESCRIPTION
[0038] In order to more clearly understand the above aspects, features and advantages of the embodiments of the present invention, the embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0039] This embodiment provides a method for preparing a modified PP material with high heat resistance and high dimensional stability. The mass ratio of each preparation raw material is the parameters in Example 1 of Table 1 below, specifically as follows:
[0040] Potassium aluminum silicate inorganic powder material is placed in a 90% ethanol solution, a quantitative silane coupling agent is added, and the potassium aluminum silicate is surface activated by high-speed stirring (3000 rpm, 10 minutes) and ultrasonic vibration (40KHz, 4 hours), and then air-dried (temperature 80°C) to obtain an activated inorganic filler A;
[0041] Introduce PP and PP-g-MAH matrix resins into a high-speed mixer and premix for 2 minutes to obtain a main material premix B;
[0042] The activated inorganic filler A and the antioxidant are introduced into a high-speed mixer for premixing at a mixing temperature of 40°C to 50°C and stirred at a low speed of 50 rpm for 5 minutes to obtain a mixture C;
[0043] The main material premix B and the mixed material C are added into the twin-screw extruder from the main feeding port and the side feeding port respectively, and the feeding speed is adjusted. The extruder temperature is 190℃-220℃, and the screw speed is 180-220 rpm. The strands are extruded, cooled and granulated to obtain a high heat-resistant modified PP material D;
[0044] First, the pellet D was dried at 70° C. for 3-5 hours in a forced air drying oven, and the specimens were prepared by injection molding at a processing temperature of 190-220° C. After the specimens were prepared, they were allowed to stand at room temperature for at least 48 hours before testing.
[0045] Table 1
[0046]
[0047] In addition, the present application also provides a plurality of comparative examples and a plurality of embodiments, and the mass ratio of the raw materials for preparing each comparative example and each embodiment is shown in Table 1 above;
[0048] In addition, it should be noted that, in the above Table 1, the total ratio of the raw materials for the preparation of each comparative example and each embodiment is 97%. Since Table 1 cannot be further enlarged, there is 3% of antioxidant in the raw materials for the preparation of each comparative example and each embodiment, that is, 3% of antioxidant is not reflected in Table 1.
[0049] Among them, the preparation method of comparative document 1 is: adding PP and antioxidant into a twin-screw extruder, and the extrusion parameters are the same as those in Example 1.
[0050] The preparation method of Comparative Example 2 is substantially the same as that of Example 1, with the only difference being that potassium aluminum silicate is replaced with mica flakes and the content is adaptively adjusted.
[0051] The preparation method of Comparative Example 3 is substantially the same as that of Example 1, with the only difference being that potassium aluminum silicate is replaced with calcium carbonate and the content is adaptively adjusted.
[0052] The preparation method of Comparative Example 4 is different from the preparation method of Example 1 in that PP-g-MAH is not contained.
[0053] The preparation methods of Examples 2 to 6 are substantially the same as that of Example 1, with the only difference being that the content is adaptively adjusted.
[0054] The preparation method of Example 7 is different from the preparation method of Example 1 in that the main ingredient premix B and the mixed material C are added to the twin-screw extruder from the main feeding port and the side feeding port respectively, and calcium carbonate is added at the same time.
[0055] The preparation method of Example 8 differs from the preparation method of Example 1 in that the main material premix B and the mixed material C are added to the twin-screw extruder from the main feeding port and the side feeding port respectively, and mica flakes are added at the same time.
[0056] The performance of the samples prepared in the above comparative examples and embodiments was tested, and the test results are shown in Table 2, Table 3 and Table 4 below:
[0057] Table 2
[0058]
[0059] Table 3
[0060]
[0061] Table 4
[0062]
[0063] Comparison of bending properties between the embodiment and the comparative example Due to the introduction of two-dimensional nano-sheet potassium aluminum silicate, the density of the high heat-resistant PP modified material changes little.
[0064] Comparison of melt flow rate between the embodiment and the comparative example. The introduction of two-dimensional nanosheet potassium aluminum silicate reduces the melt index of high heat resistance and high dimensional stability. Due to its unique structure, the slip between the layers plays a role of intermolecular lubrication. In the actual operation process, the extruder current is maintained between 7A and 8.5A, and no processing difficulties occur.
[0065] Comparison of bending performance between the embodiment and the comparative example. The introduction of two-dimensional nano-sheet potassium aluminum silicate enables the tensile strength and tensile fracture nominal strain of the high heat-resistant and high dimensional stability PP modified material to maintain a high level. Due to the unique sheet structure of potassium aluminum silicate, such as Figure 2 As shown, the molecules are stacked layer by layer, which plays a supporting and reinforcing role, thereby improving the bending resistance with high heat resistance and high dimensional stability.
[0066] Comparison of tensile properties between the embodiment and the comparative example: The introduction of two-dimensional nano-sheet potassium aluminum silicate significantly improves the bending strength and bending modulus of the PP modified material with high heat resistance and high dimensional stability.
[0067] Comparison of heat deformation temperature between the embodiment and the comparative example. The introduction of two-dimensional nano-sheet potassium aluminum silicate, due to its unique sheet structure, forms a "skeleton"-like structure in PP, which plays a certain supporting role, and because the inorganic powder itself has good heat resistance, the heat resistance of the high heat-resistant and high dimensional stability PP modified material is improved, and the heat deformation temperature is increased by 15-25°C.
[0068] Comparison of impact performance between the embodiment and the comparative example. The introduction of two-dimensional nano-sheet potassium aluminum silicate improves the simply supported beam impact strength of the high heat-resistant PP modified material. This is because when the spline undergoes brittle fracture under the condition of a sharp notch, the inorganic powder plays the role of "skeleton" support and compensation, allowing the spline to withstand more stress.
[0069] Comparison of the dimensional temperature performance of the embodiment and the comparative example: The introduction of two-dimensional nano-sheet potassium aluminum silicate significantly reduces the shrinkage of the highly heat-resistant and highly dimensionally stable PP modified material, verifying the improvement of dimensional stability.
[0070] In addition, the applicant also tested the fluidity and electrical insulation of the products of Example 2, Example 7 and Example 8. A small amount of calcium carbonate was added in Example 7, and the fluidity was better than that of the product of Example 2. A small amount of mica flakes was added in Example 8, and the electrical insulation was improved by about 10% compared with that of the product of Example 2.
[0071] The modified PP material provided in this embodiment comprises raw materials for preparing the modified PP material including a PP main material, an inorganic powder and an auxiliary agent; the mass percentage of the PP main material in the modified PP material is greater than or equal to 30% and less than or equal to 90%; the mass percentage of the inorganic powder in the modified PP material is less than or equal to 60%; the mass percentage of the auxiliary agent in the modified PP material is less than or equal to 20%; the inorganic powder comprises potassium aluminum silicate, the molecular formula of potassium aluminum silicate is SiO2·Al2O3·K2O, and the structure of potassium aluminum silicate is a lamellar structure; the auxiliary agent comprises PP-g-MAH (maleic anhydride grafted polypropylene), a coupling agent and an antioxidant.
[0072] The modified PP material provided by the present invention is prepared by adding potassium aluminum silicate to the main PP material. Since potassium aluminum silicate has a unique two-dimensional nanosheet structure, a "skeleton" support is formed, so that the modified PP material has good heat resistance and dimensional stability, which helps to improve the compressive resistance of PP when heated, and the shrinkage rate during molding is low.
[0073] In addition, the present application also adds PP-g-MAH, which serves as a compatibilizer to improve the compatibility between the PP main material and potassium aluminum silicate, thereby making the modified PP material have excellent comprehensive properties.
[0074] The coupling agent is used to activate the surface of potassium aluminum silicate, which helps to enhance the compatibility between the PP main material and potassium aluminum silicate and improve the dispersibility of inorganic powder in PP resin.
[0075] The addition of antioxidants helps to improve the aging resistance of modified PP materials.
[0076] In some embodiments, optionally, the mass percentage of the PP main material in the modified PP material is greater than or equal to 50%, and less than or equal to 70%; the mass percentage of the inorganic powder in the modified PP material is greater than 20%, and less than or equal to 40%.
[0077] In this embodiment, the content of inorganic powder is further increased, so that the addition of a large amount of inorganic powder further improves the high heat resistance, high dimensional stability, low shrinkage, high strength and other properties of the modified PP material. Of course, the content of inorganic powder cannot be too high, as too high a content of inorganic powder will reduce the content of the PP main material, thereby destroying the basic properties of the PP main material.
[0078] In some embodiments, optionally, the content of the PP main material is 50%, 60% or 70%, and the content of the inorganic powder is 20%, 30% or 40%.
[0079] In some embodiments, optionally, the coupling agent includes one or a combination of the following: silane 550 (vinyl triethoxy silane), silane 560 (γ-aminopropyl triethoxy silane), and aluminum-titanium composite coupling agent LD.
[0080] In this embodiment, silane 550, silane 560 and aluminum-titanium composite coupling agent LD are very suitable as compatibilizers between the PP main material and potassium aluminum silicate, thereby greatly improving the dispersibility of the inorganic powder in the PP resin.
[0081] In some embodiments, the antioxidant optionally includes antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) and / or antioxidant 168 (tris(2,4-di-tert-butylphenyl)phosphite).
[0082] In some embodiments, optionally, the mass percentage of PP-g-MAH in the modified PP material is less than or equal to 15%.
[0083] In this embodiment, the mass percentage of PP-g-MAH in the modified PP material is less than or equal to 15%. For example, it can be 5%-10% (it should be understood that in order to make the solution more concise and clear, the values at both ends of all ranges in this application are inclusive, 5%-10% is greater than or equal to 5%, and less than or equal to 10%, and the same applies to the other range values). For example, the mass percentage of PP-g-MAH is equal to 5%, 8% or 10%.
[0084] In some embodiments, the coupling agent may be less than or equal to 2% by mass of the modified PP material, for example, 1% or 2%.
[0085] In some embodiments, the antioxidant may be present in an amount greater than or equal to 1% and less than or equal to 3% by mass of the modified PP material, for example, 1%, 2% or 3%.
[0086] In some embodiments, optionally, the inorganic powder further includes calcium carbonate and mica flakes.
[0087] In this embodiment, the addition of calcium carbonate in an appropriate amount can improve the fluidity of the material, thereby improving its processing performance. It also helps to improve the dimensional stability of the finished product, especially reducing shrinkage during injection molding. In addition, calcium carbonate can also slightly increase the hardness and rigidity (i.e., Young's modulus) of the material. The addition of mica flakes can improve heat resistance and electrical insulation. Most importantly, the layered structure of mica flakes can form a barrier inside the material, slowing down the penetration of gases, liquids and other substances, which helps to improve the protective properties of the modified PP material.
[0088] In some embodiments, optionally, the mass proportions of potassium aluminum silicate, calcium carbonate and mica flakes are the same. Of course, the sum of the mass proportion of calcium carbonate and the mass proportion of mica flakes can also be equal to the mass proportion of potassium aluminum silicate. Of course, according to different requirements, the contents of calcium carbonate and mica flakes can also be different. Optionally, the mass proportion of calcium carbonate is 0-50, such as 5-30, such as 10-15. The mass proportion of mica flakes is 0-50, such as 5-30, such as 10-15.
[0089] In some embodiments, optionally, the thickness of the potassium aluminum silicate sheet is greater than or equal to 30 nm and less than or equal to 60 nm, and the particle size of the potassium aluminum silicate is greater than or equal to 1 μm and less than or equal to 10 μm. Optionally, the thickness of the potassium aluminum silicate sheet is greater than or equal to 40 nm and less than or equal to 50 nm, such as 40 nm or 50 nm. Optionally, the particle size of the potassium aluminum silicate is greater than or equal to 4 μm and less than or equal to 8 μm. For example, 4 μm, 6 μm or 8 μm.
[0090] In this embodiment, the thickness of the potassium aluminum silicate flakes is further limited to ensure the stability of the modified PP material when heated, and the particle size of the potassium aluminum silicate is further limited to improve the dispersibility of the potassium aluminum silicate in PP, thereby ensuring the overall comprehensive performance of the modified PP material.
[0091] In some embodiments, optionally, the grafting rate of PP-g-MAH is greater than or equal to 0.1% and less than or equal to 1.5%.
[0092] In this embodiment, if the grafting rate is too low, PP-g-MAH cannot effectively improve the compatibility between the matrix resin and the filler, resulting in uneven dispersion, which may form larger particles or agglomeration, affecting the mechanical properties, dimensional stability and heat resistance of the final product. Too high a grafting rate may increase the melt viscosity, making the material more difficult to process, such as poor flow during injection molding. Optionally, the grafting rate is equal to 1%.
[0093] Compared with the prior art, the modified PP material of the present invention has the following advantages:
[0094] 1. The modified PP material of the present invention is a blend system of polypropylene and inorganic powder. The mechanical properties and thermal properties of PP are improved and the cost is reduced through the modification of the inorganic powder.
[0095] 2. The modified PP material with high heat resistance and high dimensional stability of the present invention has high mechanical properties, such as tensile strength, tensile fracture nominal strain, bending modulus, etc., while achieving the heat resistance and low shrinkage rate, and meets practical requirements.
[0096] 3. The modified PP material of the present invention has high heat resistance and high dimensional stability. By adding potassium aluminum silicate, due to its unique two-dimensional nanosheet structure, it solves the problems of difficult mixing and large extrusion current during processing, reduces the requirements for equipment, and is conducive to industrial production.
[0097] like Figure 1 As shown, the second aspect of the present application provides a method for preparing a modified PP material, which is used to prepare a modified PP material as in any embodiment of the first aspect of the present application, and the method for preparing the modified PP material comprises:
[0098] S102: placing potassium aluminum silicate in an ethanol solution, adding a coupling agent to the ethanol solution to obtain a mixture, stirring and ultrasonically oscillating the mixture to perform surface activation treatment on the potassium aluminum silicate, and separating the activated potassium aluminum silicate;
[0099] S104: Mixing the PP main material and the PE-g-MAH to obtain a main material premix;
[0100] S106: mixing the activated potassium aluminum silicate and the antioxidant to obtain a mixed material;
[0101] S108: Extruding the main material premix and the mixed material in an extruder to obtain a modified PP material.
[0102] The preparation method of the modified PP material provided in the present application is to firstly perform surface activation on potassium aluminum silicate. Specifically, the potassium aluminum silicate inorganic powder is placed in a 90% ethanol solution, and then a quantitative silane coupling agent is added. The potassium aluminum silicate is surface activated by high-speed stirring (3000 rpm, 10 minutes) and ultrasonic vibration (40KHz, 4h), and then the activated potassium aluminum silicate is blown and dried (temperature 80°C) to obtain an activated inorganic filler A. Then, the PP main material and the PP-g-MAH matrix resin are introduced into a high-speed mixer according to the formula ratio and premixed for 2 minutes to obtain a main material premix B. Then, the activated inorganic filler A and the antioxidant are introduced into a high-speed mixer according to the ratio for premixing, the mixing temperature is 40°C-50°C, and the mixture is stirred at a low speed of 50 rpm for 5 minutes to obtain a mixed material C. Finally, the main material premix B and the mixed material C are added into the twin-screw extruder from the main feeding port and the side feeding port respectively. The feeding speed is adjusted to match the material ratio, the extruder temperature is 190℃-220℃, the screw speed is 180 rpm-220 rpm, the extrusion strands are cooled and granulated to obtain the high heat-resistant modified PP material of the present application.
[0103] A third aspect of the present invention provides a vehicle, the manufacturing material of the vehicle at least includes a modified PP material as described in any technical solution of the first aspect of the present application.
[0104] The fourth aspect of the present invention provides a battery, wherein the preparation material of the battery at least includes the modified PP material according to any technical solution of the first aspect of the present application.
Claims
1. A modified PP material, characterized in that: The raw materials for preparing the modified PP material include PP main material, inorganic powder and additives; The mass percentage of the PP main material to the modified PP material is greater than or equal to 30% and less than or equal to 90%; The mass percentage of the inorganic powder in the modified PP material is less than or equal to 60%; The mass percentage of the additive in the modified PP material is less than or equal to 20%; The inorganic powder includes potassium aluminum silicate, the molecular formula of the potassium aluminum silicate is SiO2·Al2O3·K2O, the structure of the potassium aluminum silicate is a lamellar structure, and the auxiliary agent includes PP-g-MAH, a coupling agent and an antioxidant.
2. The modified PP material according to claim 1, characterized in that: The mass percentage of the PP main material in the modified PP material is greater than or equal to 50% and less than or equal to 70%; The mass percentage of the inorganic powder in the modified PP material is greater than 20% and less than or equal to 40%.
3. The modified PP material according to claim 1, characterized in that: The coupling agent includes one or a combination of the following: silane 550, silane 560 and aluminum-titanium composite coupling agent; and / or The antioxidant includes antioxidant 1010 and / or antioxidant 168 .
4. The modified PP material according to claim 1, characterized in that: The mass percentage of the PP-g-MAH in the modified PP material is less than or equal to 15%; The coupling agent accounts for less than or equal to 2% by mass of the modified PP material; The antioxidant accounts for a mass percentage of greater than or equal to 1% and less than or equal to 3% of the modified PP material.
5. The modified PP material according to claim 1, characterized in that: The inorganic powder also includes calcium carbonate and mica flakes.
6. The modified PP material according to claim 1, characterized in that: The thickness of the potassium aluminum silicate sheet is greater than or equal to 30 nm and less than or equal to 60 nm, and the particle size of the potassium aluminum silicate is greater than or equal to 1 μm and less than or equal to 10 μm.
7. The modified PP material according to claim 1, characterized in that: The grafting rate of the PP-g-MAH is greater than or equal to 0.1% and less than or equal to 1.5%.
8. A method for preparing a modified PP material, characterized in that: Used to prepare the modified PP material as claimed in claim 1, the preparation method of the modified PP material comprises: placing potassium aluminum silicate in an ethanol solution, adding a coupling agent to the ethanol solution to obtain a mixture, stirring and ultrasonically oscillating the mixture to perform surface activation treatment on the potassium aluminum silicate, and separating the activated potassium aluminum silicate to obtain an activated inorganic filler; Mixing the PP main material and PE-g-MAH to obtain a main material premix; Mixing the activated inorganic filler and the antioxidant to obtain a mixed material; The main material premix and the mixed material are extruded in an extruder to obtain the modified PP material.
9. A vehicle, characterized in that: The vehicle is manufactured from at least one of the modified PP materials described in any one of claims 1 to 7.
10. A battery, characterized in that: The preparation material of the battery at least includes the modified PP material as described in any one of claims 1 to 7.